Analysis of physical factors of the windstorm Xaver in Poland: post-hazard review - Ribeiro, Ramos [UNESP]; Rudge, Rodrigo [UNESP]; Rucińska, Dorota (Wiley, 2017)
The windstorm Xaver, a severe wind cyclone that occurred in December 2013 caused widespread damage in many regions of Europe, including Poland where the maximum speed of wind reached 38ms−1. This paper aims to study a post event taking into consideration the forecasts and meteorological data. The analysis of the effects of the storm Xaver indicates the importance of prevention of the impacts caused by extreme natural events.